2017
DOI: 10.3310/hta21310
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomiSed controlled TRial of IntraVEnous immunoglobulin compared with standard therapy for the treatment of transverse myelitis in adults and children (STRIVE)

Abstract: Background Transverse myelitis (TM) is an immune-mediated disorder of the spinal cord that affects adults and children and that causes motor, sensory and autonomic dysfunction. There is a prolonged recovery phase, which may continue for many years. Neuromyelitis optica (NMO) is an uncommon relapsing inflammatory central nervous system condition in which TM can be the first presenting symptom. As TM and NMO affect many patients in the prime of their working life, the disorder can impose a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…IVIG has been used in various neuro-inflammatory demyelinating disorders including Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis (Gelfand, 2012; Lünemann et al, 2015; Nguyen et al, 2012; Winkelmann and Zettl, 2012), as well as immune disorders outside of the nervous system such as idiopathic thrombocytopenic purpura (ITP) and Kawasaki disease (Galeotti et al, 2010; Imbach et al, 1981; Katz-Agranov et al, 2015). Several clinical studies, albeit largely anecdotal, support the efficacy of IVIG in NMO (Bakker and Metz, 2004; Elsone et al, 2014; Magraner et al, 2013; Okada et al, 2007; Viswanathan et al, 2015; Wingerchuk, 2013); however, a recent controlled trial of IVIG in NMO transverse myelitis showed no benefit, though the study may have been underpowered (Absoud et al, 2017). We reported a modest, ~50% reduction in pathology in an experimental mouse model of NMO in which IVIG was administered at a dose that produced serum levels comparable to those in IVIG-treated humans (Ratelade et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…IVIG has been used in various neuro-inflammatory demyelinating disorders including Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis (Gelfand, 2012; Lünemann et al, 2015; Nguyen et al, 2012; Winkelmann and Zettl, 2012), as well as immune disorders outside of the nervous system such as idiopathic thrombocytopenic purpura (ITP) and Kawasaki disease (Galeotti et al, 2010; Imbach et al, 1981; Katz-Agranov et al, 2015). Several clinical studies, albeit largely anecdotal, support the efficacy of IVIG in NMO (Bakker and Metz, 2004; Elsone et al, 2014; Magraner et al, 2013; Okada et al, 2007; Viswanathan et al, 2015; Wingerchuk, 2013); however, a recent controlled trial of IVIG in NMO transverse myelitis showed no benefit, though the study may have been underpowered (Absoud et al, 2017). We reported a modest, ~50% reduction in pathology in an experimental mouse model of NMO in which IVIG was administered at a dose that produced serum levels comparable to those in IVIG-treated humans (Ratelade et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study on 10 NMOSD patients unresponsive to IVMP, IVIgG was effective in 50% of patients [ 87 ]. Unfortunately, a multicenter, single-blind, parallel-group, RCT on IVIG compared to standard therapy for TM treatment in adults and children (STRIVE study [NCT02398994]) was discontinued due to difficulties recruiting patients [ 88 ]. Recently, a retrospective study reported high-dose IVMP plus IVIgG was superior to high-dose of IVMP alone [ 89 ].…”
Section: Treatment Of Neuromyelitis Optica Spectrum Disordersmentioning
confidence: 99%
“…Binding induces an immune response that causes lysis of B cells. NPB-01 (NCT01845584) Intravenous immunoglobulin 400 mg/kg/day for five consecutive days IgG can inactivate auto-reactive T-cells by competing for, and interrupting their interaction with, antigen presenting cells [ 87 , 88 ]. HBM 9161 (NCT04227470) injection, 340 mg or 680 mg weekly administered subcutaneously for a period of 4 weeks.…”
Section: Treatment Of Neuromyelitis Optica Spectrum Disordersmentioning
confidence: 99%
“…Kleiter and colleagues 35 also reported 4 AQP4‐IgG NMOSD attacks treated with IVIG, but therapy was combined with other treatments making interpretation of IVIG alone difficult. Disappointingly STRIVE, a randomized clinical trial, comparing IVMP vs IVMP and IVIG in acute TM, failed to recruit sufficient participants to reach its primary endpoint 44 . Further studies will be required to determine if IVIG is beneficial in MOGAD and other in CNS inflammatory disease.…”
Section: Acute Attack Treatmentsmentioning
confidence: 99%
“…35,43 Improvement was noted in 5 of 11 (45.5%) of steroid and PLEXrefractory AQP4-IgG NMOSD relapses (bilateral ON, 4; LETM, 7); with median pretreatment EDSS of 7 (4-9) and posttreatment EDSS of 6.5 (3-9) approximately 2 months later. 43 44 Further studies will be required to determine if IVIG is beneficial in MOGAD and other in CNS inflammatory disease.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%